High frequency trading and mini flash crashes - Anton Golub; John Keane; Ser Huang Poon (The University of Manchester, Manchester Business School, 2012)
We analyse all Mini Flash Crashes (or Flash Equity Failures) in the US equity markets in the four most volatile months during 2006-2011. In contrast to previous studies, we find that Mini Flash Crashes are the result of regulation framework and market fragmentation, in particular due to the aggressive use of Intermarket Sweep Orders and Regulation NMS protecting only Top of the Book. We find strong evidence that Mini Flash Crashes have an adverse impact on market liquidity and are associated with Fleeting Liquidity.
Keywords: 330; Mini Flash Crash; Flash Crash; Liquidity; High Frequency Trading; Intermarket Sweep Order; Top of the Book Protection; Regulation National Market System